EMPOWERMENT OF TAMBAK FARMERS GROUPS IN COMMUNITY ECONOMIC DEVELOPMENT IN THE VILLAGE PADANG SAKTI - Khairawati; Wahyu Fuadi; Eva Ayuzar; Nurainun; Rahmaniar (RADJA PUBLIKA, 2023)
The problems faced by the pond farmer group partners are very complex, namely from the macro production aspect where the limitations of the shrimp cultivation technology applied are still very traditional, large areas of land but not yet properly utilized, expensive feed costs, lack of business capital, while at the micro level they are constrained by limitations in mastery. technology and shrimp cultivation process with the latest technology. The marketing management aspect is still traditional where the harvest is only sold in local markets and also to agents who buy directly from farms so that their sales turnover is not too large. Aspects of Business Management where the harvest results are not utilized properly in empowering the community's economy. The aim of implementing environmentally assisted village service activities in Padang Sakti Village, Muara Satu District is to find solutions to the problems faced by partners in empowering and developing the economy of the pond farmer group community. The approach method that will be used in providing solutions to problems faced by partners by providing knowledge is by providing training/counseling and mentoring with the use and application of good and correct shrimp farming management cultivation technology, correct marketing management by utilizing information technology to carry out online promotions so that harvest results can be distributed properly as well as providing training on processing pond products to make healthy food at economical prices which can empower the community's economic income. Based on the implementation of community service programs in environmentally assisted villages that have been implemented smoothly, the Meuhasae farmer group, Padang Sakti Village, Muara Satu District, is very enthusiastic in participating in training, mentoring and playing an active role in asking discussion questions or sharing knowledge with the material provided both in terms of management. aquaculture and from a marketing perspective. It is hoped that the results from the shrimp farming sector will improve and the harvest results will be able to help partners in increasing the income of the Partner group.